Outcomes of endoscopic ultrasound-guided ablation and minimally invasive surgery in the treatment of pancreatic insulinoma: a systematic review and meta-analysis - Xiao, Dan; Zhu, Li; Xiong, Si; Yan, Xu; Jiang, Qin; Wang, Ao; Jia, Yegui (Frontiers in Endocrinology, 2024)
Background and Aims: Most pancreatic insulinomas can be treated by minimally invasive modalities. The aim of this meta-analysis was to assess the clinical outcomes of endoscopic ultrasound (EUS)-guided ablation and minimally invasive surgery (MIS) in the treatment of pancreatic insulinoma. Materials and Methods: Online databases were searched for relevant studies. The primary aim was to compare the rates of adverse events (AEs) and the secondary aims were to compare the clinical and technical success rates, length of hospital stays, and symptom recurrence rates between EUS and MIS approaches. Results: Eight studies with 150 patients were identified that reported EUS-guided ablation outcomes, forming the EUS group, and 9 studies with 236 patients reported MIS outcomes, forming the MIS group. The pooled median age of the included patients in the EUS group was greater than that of the MIS group (64.06 vs. 44.98 years old, p < 0.001). Also, the technical success rate was significantly higher in the EUS group (100% vs. 96.6%, p = 0.025), while the clinical success was significantly higher (6%) in the MIS group (94% vs. 98.7%, p = 0.021). The AE rates (18.7% vs. 31.1%, p = 0.012) and severe AE rates (1.3% vs. 7.9%, p = 0.011) were significantly lower in the EUS group. The median length of hospital stay in the EUS group (2.68 days, 95% CI: 1.88–3.48, I2 = 60.3%) was significantly shorter than in the MIS group (7.40 days, 95% CI: 6.22–8.58, I2 = 42.2%, p < 0.001). The recurrence rate was significantly higher in the EUS group (15.3% vs. 1.3%, p < 0.001). Conclusion: EUS-guided ablation is associated with a lower AE rate and a shorter length of hospital stay, but a higher recurrence rate for the treatment of insulinoma compared with MIS. The EUS approach may be an alternative, even first-line, treatment for poor surgery candidates.